The effects of trauma on intimate relationships: A qualitative study with clinical couples - Goff, Briana S. Nelson; Reisbig, Allison M.J.; Bole, Amy; Scheer, Tamera; Hayes, Everett; Archuleta, Kristy L.; Henry, Stacey Blalock; Hoheisel, Carol B.; Nye, Ben; Osby, Jamie; Sanders-Hahs, Erin M.; Schwerdtfeger, Kami L.; et al. (My University, 2006)
Research has traditionally focused on the development of symptoms in those who experienced trauma directly but has overlooked the impact of trauma on victims' families. In recent years, researchers and clinicians have begun to examine how individual exposure to traumatic events affects the spouses or partners, children, and professional helpers of trauma survivors. The current study examines qualitative interview data from 17 individuals, analyzed using a retroductive methodology to identify how intimate relationships are affected when there is a history of trauma exposure. The following primary themes were identified: increased communication, decreased communication, increased cohesion/connection, decreased cohesion/connection, increased understanding, decreased understanding, sexual intimacy problems, symptoms of relationship distress, support from partner, and relationship resources. Areas for future research and clinical implications are identified.
Keywords: Traumatic stress; Trauma exposure; Couples; Intimate relationships